Susceptibility of dental caries microcosm biofilms to photodynamic therapy mediated by fotoenticine - Garcia, Maíra Terra [UNESP]; Ward, Rafael Araújo da Costa [UNESP]; Gonçalves, Nathália Maria Ferreira [UNESP]; Pedroso, Lara Luise Castro [UNESP]; Neto, José Vieira da Silva; Strixino, Juliana Ferreira; Junqueira, Juliana Campos [UNESP] (MDPI, 2021)
Photodynamic therapy (PDT) mediated by Fotoenticine® (FTC), a new photosensitizer derived from chlorin e-6, has shown in vitro inhibitory activity against the cariogenic bacterium Streptococcus mutans. However, its antimicrobial effects must be investigated on biofilm models that represent the microbial complexity of caries. Thus, we evaluated the efficacy of FTC-mediated PDT on microcosm biofilms of dental caries. Decayed dentin samples were collected from different patients to form in vitro biofilms. Biofilms were treated with FTC associated with LED irradiation and analyzed by counting the colony forming units (log10 CFU) in selective and non-selective culture media. Furthermore, the biofilm structure and acid production by microorganisms were analyzed using microscopic and spectrophotometric analysis, respectively. The biofilms from different patients showed variations in microbial composition, being formed by streptococci, lactobacilli and yeasts. Altogether, PDT decreased up to 3.7 log10 CFU of total microorganisms, 2.8 log10 CFU of streptococci, 3.2 log10 CFU of lactobacilli and 3.2 log10 CFU of yeasts, and reached eradication of mutans streptococci. PDT was also capable of disaggregating the biofilms and reducing acid concentration in 1.1 to 1.9 mmol lactate/L. It was concluded that FTC was effective in PDT against the heterogeneous biofilms of dental caries.
Keywords: Chlorine; Dental caries; Fotoenticine; Methylene blue; Oral biofilms; Photodynamic therapy